2013
DOI: 10.18869/acadpub.rmm.1.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of EPIYA motifs in Helicobacter pylori strains isolated from patients with gastroduodenal disorders in northern Iran

Abstract: Background: Cytotoxin-associated gene A (CagA)-positive strains of Helicobacter pylori are associated with gastroduodenal diseases. Evidences have suggested that the type of H. pylori CagA EPIYA motifs may be associated with recurrent dyspepsia (i.e. gastritis, peptic ulcer, or gastric cancer). We investigated the prevalence of different EPIYA motifs (A, B, C, or D) in H. pylori strains isolated from patients with recurrent dyspepsia who underwent upper gastrointestinal (GI) endoscopy. We investigated the prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Qadri et al (2014) found that 70 % of CagA-positive GC cases had more than one EPIYA-C repeat. Ajami et al (2013) found EPIYA-ABCC in 36.2 % of the patients with GC, and patients with EPIYA-C had a 2.27-fold increase in GC development versus patients with DU. Again, Kalaf et al (2013) indicated that more than one EPIYA-C repeat occurred in 66.6 % of GC patients.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Qadri et al (2014) found that 70 % of CagA-positive GC cases had more than one EPIYA-C repeat. Ajami et al (2013) found EPIYA-ABCC in 36.2 % of the patients with GC, and patients with EPIYA-C had a 2.27-fold increase in GC development versus patients with DU. Again, Kalaf et al (2013) indicated that more than one EPIYA-C repeat occurred in 66.6 % of GC patients.…”
Section: Discussionmentioning
confidence: 88%
“…This may be explained by the difference in H. pylori virulence factors rather than H. pylori infection rate (Yamaoka, 2010). There is strong evidence that CagA functions as a bacterial oncoprotein in mammals (Wroblewski et al, 2010), and CagA-positive H. pylori strains have been suggested to increase the risk of developing atrophic gastritis and GC by several researchers (Huang et al, 2003;Sahara et al, 2012;Ajami et al, 2013). As indicated by several studies, phosphorylated CagA-SHP-2 interactions contribute to cytoskeletal rearrangements and cell elongation by stimulating the ERK-MAP kinase signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that circulating strains among Iranian patients originate from hpEurope strains, and have transferred to Iran from some groups such as Arabs in the 7-8th centuries, Uzbeks ght in 16th century, and Ottoman Empire during the 20th century (86). Existence of cagA2a genotype (EPIYA-ABC motifs) in Iran's studies con rm this hypothesis (37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47). However, why the number of gastric cancer cases in Iran is as high as cases of Japan, South Korea, and China?…”
Section: Discussionmentioning
confidence: 87%
“…In general, cagA genotypes recognized from around the world include AB, ABC, ABCC, ABCCC, ABCCCC, and ABD. In studies from Iran, so far there is no any document based on detection of cagA genotypes ABCCCC and ABD, which is arising from genetic differences between isolated strains of Iranian patients and East Asian's strains (37)(38)(39)(40)(41)(42)(43)(44)(45)(46). Nevertheless, according to studies, in Iran, cagA genotypes ABCC and ABCCC are more prevalent in peptic ulcer and gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 35 These findings suggest an important role for cag-positive H. pylori strains in the production of angiogenic factors that lead to cancer metastasis. 15 Although we did not examine the presence of cag in our samples, the prevalence of cag positive H. pylori strains is approximately 57% in patients infected with H. pylori , based on a 2012 study by Ajami et al 36 in the north of Iran.…”
Section: Discussionmentioning
confidence: 97%